Early postoperative serum carcinoembryonic antigen levels in patients operated for colorectal carcinoma - Veingerl, Bojan (Radiology and oncology (Ljubljana), 2003)
Background. The only method of treatment offering a favourable prognosis for colorectal carcinoma is radical resection of the part of the colon or rectum including the pertaining lymph nodes and eventual radical removal of metastases. But even such presumably curative surgery does not warrant full recovery of all operated patients as recurrences are frequent and according tomost analyses 5-year survival is lower than 50%. Therefore, additional treatment is attempted in some patients. Various prognostic factor of disease recurrance are helful. One such prognostic sign is serum carcinoembryonic antigen (CEA) level measured soon after surgery. Conclusions. All patients with radical R0 resection, according to their postoperative serum CEA levels and the CEA half-life fall into three groups: CEA R0, CEA R1, and CEA R2 resected patients. A statistically significant difference regarding survival and number of recurrence was noted among patients categorized bz the stage of disease, particularly between the three groups of patients and the group having been undergone presumably curative surgery.
Keywords: Blood; Carcinoembryonic Antigen; Colorectal Neoplasms; črevesje; črevesne bolezni; diagnostika; Follow-Up Studies; Genetics; Karcinoembrionalni antigen; Kolorektalne novotvorbe; Prognosis; Prognoza; rak (medicina); Sledilne študije; Surgery